Transformasi Pembelajaran Laboratorium: Peningkatan Keterampilan Eksperimen dan Adaptasi Terhadap Tantangan Pembelajaran Abad 21 - Lestari, Wulan; Malik, Adam (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
In the modern era of education, the significance of laboratory learning extends beyond physical experiments to the development of essential skills for students facing the challenges of the 21st century. This article examines the transformation of laboratory learning through project-based approaches and the integration of digital technology. Research indicates that these approaches enhance students' practical skills and conceptual understanding, while preparing them for dynamic, technology-driven work environments. Literature reviews underscore the importance of adapting laboratory curricula to incorporate 21st-century skills such as critical thinking and creativity. Moreover, the use of virtual laboratories and computer simulations has proven effective in facilitating safe and controlled practical learning, particularly amidst the COVID-19 pandemic. This transformation supports the vision of laboratories as holistic and dynamic learning environments, equipping students with relevant and robust skills to meet future challenges. Keywords: laboratory learning, transformation, digital technology.